THE EFFECT OF PROFITABILITY AND LIQUIDITY ON DIVIDEND POLICY OF MULTINATIONAL COMPANIES IN INDONESIA IN THE CONSUMER GOODS SECTOR - Ramandha, Raiqah Inayah; Sahabuddin, Romansyah; Anwar, Anwar; Nurman, Nurman; Musa, Muhammad Ichwan (Universitas Negeri Makassar, 2025)
Abstract: This study aims to analyze the effect of profitability and liquidity on dividend policy in multinational companies in the consumption sector listed on the Indonesia Stock Exchange (IDX), both partially and simultaneously. The sample of this study uses a purposive sampling technique for the period 2019 to 2023, consisting of 13 selected multinational companies in the consumption sector. The method used in this study is a quantitative research method with an explanatory approach. This study uses multiple linear regression analysis to test the effect of independent variables on the dependent variable. The multiple regression analysis uses SPSS 26. The results of the study indicate that Return On Assets (ROA) does not have a significant effect with a significance value of 0.729 on the dividend policy of multinational companies in the consumption sector listed on the IDX. Conversely, the Current Ratio (CR) does not have a significant effect on dividend policy with a significance value of 0.575. Simultaneously, the regression model tested shows that the F statistic value indicates that the correlation between the independent variables is not strong enough to explain the dependent variable or is not significant.Keywords: Profitability, Liquidity, Dividend Policy